2011
DOI: 10.1111/j.1365-2958.2011.07632.x
|View full text |Cite
|
Sign up to set email alerts
|

SEC14 is a specific requirement for secretion of phospholipase B1 and pathogenicity of Cryptococcus neoformans

Abstract: Summary Secreted phospholipase B1 (CnPlb1) is essential for dissemination of Cryptococcus neoformans to the central nervous system (CNS) yet essential components of its secretion machinery remain to be elucidated. Using gene deletion analysis we demonstrate that CnPlb1 secretion is dependent on the CnSEC14 product, CnSec14-1p. CnSec14-1p is a homologue of the phosphatidylinositol transfer protein (PITP) ScSec14p, which is essential for secretion and viability in Saccharomyces cerevisiae. In contrast to CnPlb1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
95
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 90 publications
(101 citation statements)
references
References 50 publications
(100 reference statements)
4
95
2
Order By: Relevance
“…The correlation between in vitro phospholipase B activity of cryptococcal strains and virulence in mice was first demonstrated in 1997 (Chen et al 1997) and subsequent work with phospholipase B gene (PLB1)-deletion strains confirmed the importance of the enzyme as a virulence determinant Noverr et al 2003). Phospholipase B is transported to the cell surface in vesicles (Eisenman et al 2009) and its secretion is dependent upon Sec14, a phosphatidylinositol transfer protein (Chayakulkeeree et al 2011). Transport of the enzyme to the cell surface enhances adhesion of the cryptococcal cells to human lung epithelial cells, the first step toward initiation of interstitial pulmonary cryptococcosis (Ganendren et al 2006).…”
Section: Degradation Enzymesmentioning
confidence: 95%
See 1 more Smart Citation
“…The correlation between in vitro phospholipase B activity of cryptococcal strains and virulence in mice was first demonstrated in 1997 (Chen et al 1997) and subsequent work with phospholipase B gene (PLB1)-deletion strains confirmed the importance of the enzyme as a virulence determinant Noverr et al 2003). Phospholipase B is transported to the cell surface in vesicles (Eisenman et al 2009) and its secretion is dependent upon Sec14, a phosphatidylinositol transfer protein (Chayakulkeeree et al 2011). Transport of the enzyme to the cell surface enhances adhesion of the cryptococcal cells to human lung epithelial cells, the first step toward initiation of interstitial pulmonary cryptococcosis (Ganendren et al 2006).…”
Section: Degradation Enzymesmentioning
confidence: 95%
“…neoformans produces many degradation enzymes; some of them have been confirmed as virulence determinants. Urease (Cox et al 2000Osterholzer et al 2009;Shi et al 2010;Bahn and Jung 2013;Singh et al 2013) and phospholipase B Ganendren et al 2006;Wright et al 2007;Chayakulkeeree et al 2011) are the two most studied degradation enzymes that have a role in cryptococcal pathogenicity. The functions of these enzymes promote intracellular survival of the yeasts (Wright et al 2007), hydrolysis of host cell membranes to penetrate into tissue (Chen et al 1997), immunomodulation (Noverr et al 2003;Osterholzer et al 2009), and the enhancement of fungal dissemination from the lung to the brain (Cox et al 2000;Noverr et al 2003;Wright et al 2007;Shi et al 2010;Singh et al 2013).…”
Section: Degradation Enzymesmentioning
confidence: 99%
“…In this study, we demonstrated a previously unknown function of flippases in physiological and pathogenic secretion-related events used by C. neoformans. To the best of our knowledge, cryptococcal regulators of secretion described so far include the products of the SEC (51,58,64) and CAP genes (65-70), Golgi reassembly and stacking protein (30), protein kinase A (71), vacuolar Ca 2ϩ transporters (35,59), and the vacuolar protein Vps23 (72). Mutants with altered expression of the genes coding for each of these secretory regulators are hypovirulent or avirulent in mice.…”
Section: Discussionmentioning
confidence: 99%
“…In murine models of infection with C. neoformans strain H99 and deletion mutants, Plb1 and laccase are essential for the egress of cryptococci from the lung and dissemination via the blood to the CNS (143,144). Plb1 and urease are required to establish cerebral cryptococcosis, urease promotes the migration of cryptococci across the blood-brain barrier (BBB) (143)(144)(145)(146), and Plb1 is required for the extrusion of C. neoformans from macrophages (147). Urease has also been reported to promote an anti-inflammatory Th2 cellular response in the lung (148).…”
Section: Cryptococcal Virulence Determinantsmentioning
confidence: 99%